MODERNIZATION OF EDUCATION: IMPACT ON SOCIAL SYSTEM DEVELOPMENT - Nadezhda F. Yefremova (Advanced Engineering Research, 2012)
General laws of self-organization, certain features of the integral systems, relationship of the socioeconomic and socio-educational systems development in their unity, similarity and difference, are considered.